Health Impact Assessment of Urban Agriculture in Kampala - Nasinyama, George W.; Cole, Donald C.; Smith, Diana Lee (Springer, New York, NY, 2010)
While the Urban Harvest-supported studies described in the previous three chapters were going on in Kampala, an opportunity arose to complement them with an exploration of the health impacts associated with urban agriculture (UA) in the city. The Kampala City Council had expressed concern about the health risks associated with some forms of UA and the research team welcomed the chance to examine ways to reduce health risks and increase health benefits. A parallel research process was therefore set up, governed by a Health Coordinating Committee comprising researchers and policy-makers. Scholars from universities and research institutes in Uganda and Canada, in collaboration with local government and non-governmental organizations, were supported by the Canadian International Development Agency (CIDA) and the International Development Research Centre (IDRC). This chapter is essentially a summary of a companion book titled “Healthy City Harvests: generating evidence to guide policy on urban agriculture”, which contains all these studies (Cole et al. 2008). As in that book, the research findings are translated into policy implications, not only for Kampala but also for other cities with similar conditions.
Keywords: Leafy Vegetable; Urban Agriculture; Chicken Meat; Health Impact Assessment; Household Food Security